(untitled) (The Review of Diabetic Studies, 2019)
BACKGROUND: Abdominal obesity is characterized by low-grade inflammation and plays a central role in the development of type 2 diabetes and cardiovascular diseases. Dietary factors can influence low-grade inflammation and affect adipose tissue function. AIM: To investigate the separate and combined effects of whey protein and cereal fiber on inflammatory markers and adipose tissue gene expression in abdominal obesity. METHODS: We performed a 12-week, double-blind, randomized controlled dietary intervention in 65 adults with abdominal obesity. The participants were randomized to 4 groups using a 2 × 2 factorial design; they received either 60 g/day of whey protein or maltodextrin in combination with high-fiber wheat bran products (30 g fiber/day) or low-fiber refined wheat products (10 g fiber/day). Plasma concentrations of tumor necrosis factor α (TNF-α), high-sensitivity C-reactive protein (hs-CRP), monocyte chemoattractant protein-1 (MCP-1), interleukin 1 receptor antagonist (IL-1Ra), and adiponectin were measured before and after intervention. Changes in gene expression related to inflammation, insulin signaling, and lipid metabolism were measured in abdominal subcutaneous adipose tissue. RESULTS: After intervention, TNF-α was reduced for both high-fiber groups compared with baseline, but did not significantly differ from the low-fiber groups. There were no differences in fasting or postprandial inflammatory markers between the groups. The relative gene expression of ribosomal protein S6 kinase B1 (S6K1) was increased after whey protein compared with maltodextrin consumption. CONCLUSION: Intake of whey protein in combination with high cereal fiber content did not differentially affect low-grade inflammation or adipose tissue gene expression compared with maltodextrin and low fiber content in individuals with abdominal obesity.